Species Listing of Macrofungi in Brgy. Zabali, Baler, Aurora, Philippines (Biosaintifika: Journal of Biology & Biology Education, 2026)
Macrofungi are often perceived as uncharismatic and, hence, are frequently neglected in scientific discussions on wildlife conservation. Several macrofungal studies have been conducted in various parts of the Philippines, most particularly in Luzon. This paper reports the species found in the ultramafic forests of Brgy. Zabali, Baler, Aurora, one of the key biodiversity areas of the Philippines. Particularly, the study aimed to observe the composition of macrofungi during the transition period towards the southwest monsoon (habagat season). An opportunistic sampling method was employed in the study across three collection periods from May to July 2025. We found that the forests of Brgy. Zabali support a diverse array of macrofungal species and are substantially influenced by precipitation. Polyporoid fungi were the dominant species during drier periods, while many fleshy fungi emerged much later, upon an increase in rainfall. A total of 105 specimens were collected, which are categorized under 1 class, 8 orders, 24 families, 39 genera, and 52 species. The family Polyporaceae recorded the highest number of distinct species among other families. Out of 52 species, only 19 were identified to the species level. The study also reports seven (7) newly recorded basidiomycetes in the Philippines, namely, Calocera sp., Laetiporus sp. Marasmius cf. cladophyllus, Panus c.f similis, Phaeotremella sp., Phylloporia cf. alyxiae, and Scleroderma sp. The absence of ascomycete representatives in the study may be attributed to poor timing and a relatively short collection period. Nevertheless, the results of this study provide valuable insights into the long-term monitoring and conservation of Philippine macrofungi.